Virtual reality as narrative medium: the emotional effects of full immersion in VR-based film Aladin - Arvina Dwi Romadhani (Asosiasi Relawan dan Pengelola Jurnal LPTNU (ARJUNU), 2025)
Background: Virtual Reality (VR) has emerged as a transformative medium, offering immersive storytelling experiences compared to traditional 2D films. Objective: This study aims to compare emotional and physiological responses elicited by Virtual Reality (VR) and Youtube (YT) versions of Aladin: Escape the Cave of Wonders. Method: Using a mixed-methods approach, emotional data were collected through PANAS (Positive and Negative Affect Schedule), while physiological responses such as skin temperature (SKT), heart rate (HR), and respiratory patterns were recorded. Results: Results indicate that VR elicits stronger emotional engagement, with significant increases in negative affect (e.g., fear and nervousness) and higher HR compared to YT films. Scene-specific analyses reveal that immersive environments amplify emotions during intense scenes, supported by physiological markers of heightened arousal. Implication: This research advances the understanding of how immersive media like VR can redefine narrative engagement, with implications for fields ranging from media psychology to digital storytelling. Novelty: This study underscores VR’s potential as a narrative medium and provides insights into its application for enhancing audience engagement across genres.